Occupational safety and health knowledge users' perspectives about research use. Issue 1 (2nd January 2018) - Van Eerd, Dwayne; Cardoso, Siobhan; Irvin, Emma; Saunders, Ron; King, Trevor; Macdonald, Sara
Abstract: Using research evidence in decision-making requires skill, time and resources. Our objective was to examine experiences and perspectives related to research use among occupational safety and health (OSH) knowledge users (KU). This was a qualitative study investigating how research was acquired, assessed, adapted and applied in decision-making. A purposive sample of OSH KU was invited to complete an online survey and/or participate in interviews or focus groups. Most OSH KU indicated using research evidence was important. KU reported having skills and motivation to find and evaluate research. KU also reported sharing evidence with a variety of audiences. Time and resources were consistently noted as barriers. Credibility was an overarching theme as KU wanted to use credible research and noted their own credibility relied on using research in their work. KU were creative in using research in their OSH roles. More research with a broader audience of OSH KU is needed.